1994
DOI: 10.3892/or_00000069
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the lateral sentinel node by indocyanine green for rectal cancer based on micrometastasis determined by reverse transcriptase-polymerase chain reaction

Abstract: Abstract. The significance of dissecting the lateral pelvic lymph node (LN) for lower rectal cancer remains controversial. We detected the lateral sentinel node (SN) by indocyanine green (ICG) and micrometastases using carcinoembryonic antigen (CEA)-specific reverse transcriptase-polymerase chain reaction (RT-PCR). Twenty-five patients who underwent curative surgery with a dissection of the lateral pelvic LNs between 2003 and 2005 were examined. We investigated the existence of lateral SNs and any associations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…ICG fluorescence imaging can potentially be used for (1) sentinel lymph node detection;6,7 (2) evaluation of lymphedema;8 (3) microvascular circulation of free flaps in reconstructive surgery;9 and (4) endoscopic marking of colorectal tumors 7…”
Section: Discussionmentioning
confidence: 99%
“…ICG fluorescence imaging can potentially be used for (1) sentinel lymph node detection;6,7 (2) evaluation of lymphedema;8 (3) microvascular circulation of free flaps in reconstructive surgery;9 and (4) endoscopic marking of colorectal tumors 7…”
Section: Discussionmentioning
confidence: 99%
“…In colorectal cancers, Noura et al55 initially mapped SLN in 25 lower rectal cancer patients using ICG as a dye. In this study, the SLN was detected in only 7 of 25 (28%) patients.…”
Section: Intraoperative Sln Mapping and Biopsy Using Icgmentioning
confidence: 99%
“…In this study, the SLN was detected in only 7 of 25 (28%) patients. The authors suggested that this may be for 3 possible reasons: advanced stage of the rectal cancer, inability to intraoperatively trace the lymph node, and macroscopic detection of SLNs 55. The desire to improve the method of SLN detection resulted in another study by Noura et al, where SLN detection was analyzed in 25 patients with lower rectal cancers, but using ICG as a fluorophore.…”
Section: Intraoperative Sln Mapping and Biopsy Using Icgmentioning
confidence: 99%
“…37 In rectal cancer the detection rate of the SLN appeared to be very low; only in seven out of 25 patients (28%) could the SLN be detected. 38 …”
Section: A C C E P T E D Article In Pressmentioning
confidence: 99%